2021
DOI: 10.31842/jurnalinobis.v4i4.196
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Company Value: A Manufacturing Industry Case Study

Abstract: The purpose of this research is to look into the impact of corporate governance in the Indonesia Stock Exchange's Manufacturing Industry. Panel data from 73 Manufacturing Industry companies on the Indonesia Stock Exchange from 2014 to 2018 with a total of 365 observations of data whose research results were analyzed using panel data regression analysis with the Random Effect Model approach. Institutional ownership has a positive effect on Tobin's q and market book value, according to the study's findings. Tobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The positive sign of the regression coefficient indicates a positive relationship between the number of board of commissioners and the firm's worth, implying that an increase in the former tends to result in an increase in the latter. This finding contrasts the statement that the board of commissioners, as the highest supervisor, significantly increases company value (Malini et al, 2021;Oktari et al, 2018). In conditions where Covid-19 is spreading, the board of commissioners, which functions as the highest supervisor of the company (as measured by the size of its members and the independence of the members of the board of commissioners), cannot function effectively.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The positive sign of the regression coefficient indicates a positive relationship between the number of board of commissioners and the firm's worth, implying that an increase in the former tends to result in an increase in the latter. This finding contrasts the statement that the board of commissioners, as the highest supervisor, significantly increases company value (Malini et al, 2021;Oktari et al, 2018). In conditions where Covid-19 is spreading, the board of commissioners, which functions as the highest supervisor of the company (as measured by the size of its members and the independence of the members of the board of commissioners), cannot function effectively.…”
Section: Discussioncontrasting
confidence: 60%
“…The presence of Independent Commissioners is crucial for a company's overall value, as Independent Commissioners can play a role in resolving conflicts by communicating shareholder objectives to the management. As companies face increasing complexity and challenges, internal company commissioners have several limitations, not only in terms of their level of independence but also due to the quality of individual internal commissioners (Malini et al, 2021). The presence of Independent Commissioners is continually reinforced to ensure their effectiveness, often with the support of an Audit Committee (Malini et al, 2021), and studies like (Oktari et al, 2018) have shown that Independent Commissioners do indeed have an impact on firm value.…”
Section: Introductionmentioning
confidence: 99%
“…This study also shows that return on assets can mediate the relationship between the current ratio to price to book value, and return on assets cannot mediate the relationship between debt to equity ratio to price to book value. Helma Malini, Dyen Natalia, Giriati Giriati's (2021) research results show that institutional ownership has a positive effect on Tobin's q and market book value, Tobin's q and market book value is negatively affected by foreign ownership, Board of Commissioners and Audit Committee meetings harm stock price returns, meetings of the board of directors, audit committee, and the board of commissioners have no impact on firm value. Based on these findings, it can be concluded that the results of testing the independent variables on the dependent are not convincing and need to be questioned further.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research from Alabdullah and Ahmed (2020), Al-Okaily and Naueihed (2020), Azam and Wang (2021), and Özcan (2021) found that there is a positive influence of the audit committees on firm value. Malini et al (2021) failed to find the effect of the audit committee on firm value, while Al-Jalahma (2022) found a negative effect of the audit committee on firm value.…”
Section: Hypotheses Developmentmentioning
confidence: 99%